2011
DOI: 10.1080/10286608.2011.637625
|View full text |Cite
|
Sign up to set email alerts
|

Decision analysis for a tsunami detection system – case study: Sri Lanka

Abstract: The massive devastation of the Indian Ocean mega tsunami in 2004, clearly calls for an efficient early warning system for the Indian Ocean countries. The 'Regional Watch Provider' system currently planned makes some countries entirely dependent on the watch providers. We discuss a feasible and reliable tsunami detection mechanism for Sri Lanka that would give it some independent information for decision making purposes. It contemplates Sri Lanka deploying its own additional detection tools. A stand-alone tide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A reassessed reliability eight years after the original study remains the same. With respect to tsunami buoys, Wickramaratne et al (2011a, 2011b) presented a range of 79-92 per cent. With the increased number of buoys and heightened technology associated with DART (Deep-ocean Assessment and Reporting of Tsunamis) buoys, the reliability is reassessed based on available data from the US National Data Buoy Center (NDBC).…”
Section: Probabilities Of Tsunami Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A reassessed reliability eight years after the original study remains the same. With respect to tsunami buoys, Wickramaratne et al (2011a, 2011b) presented a range of 79-92 per cent. With the increased number of buoys and heightened technology associated with DART (Deep-ocean Assessment and Reporting of Tsunamis) buoys, the reliability is reassessed based on available data from the US National Data Buoy Center (NDBC).…”
Section: Probabilities Of Tsunami Detectionmentioning
confidence: 99%
“…The activities involved in each of the above elements can be made to form a network which then can be simulated to derive stochastic estimates of time taken to evacuate a particular location from the point of triggering the earthquake/tsunami. From the initial work of Fernando et al (2008), there has been a progressive development of simulating the TWE network pertaining to the Indian Ocean region (Ruwanpura et al , 2009; Wickramaratne et al , 2009, 2011a, 2011b).…”
Section: Tsunami Warning and Evacuation Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] Wickramaratne et al (2011) indicated that "successful evacuation is the ultimate decisive factor of the whole warning process since an incomplete evacuation could cause thousands of lives to be lost." [22] In Taiwan, disaster relief roads are defined in the following manner: those 8 m or more in width are for emergency evacuation; those 15 m or more in width are for firefighting, emergency response, and rescue; and those 20 m or more in width are for material supplies, external communications, support, and emergency shelter, if necessary. [19] The outward access conditions of a shelter determine the disaster management functions.…”
Section: Technical Perspectivementioning
confidence: 99%